Counter-Protective Role for Interleukin-5 during Acute Toxoplasma gondii Infection - Nickdel, M. B. (American Society for Microbiology, 2001)
The role of interleukin-5 (IL-5) during Toxoplasma gondii infection was investigated by comparing disease progression in IL-5 gene deficient (IL-5−/−) mice and their wild-type (WT) counterparts on a C57BL/6 background. IL-5−/− mice infected orally with T. gondii were less susceptible to infection than WT mice as demonstrated by reduced mortality rates. Consistent with this data, orally infected IL-5−/− mice had less severe pathological changes in their small intestines than WT mice at 8 days postinfection. At this time, splenocytes and mesenteric lymph node cells derived from IL-5−/− mice produced levels of IL-12, interferon-γ (IFN-γ), IL-4, IL-10, and nitric oxide (measured as nitrite) similar to those derived from WT mice when stimulated with Toxoplasma lysate antigen. However, peak serum IL-12 and IFN-γ levels (at days 6 and 8, respectively) were significantly higher in IL-5−/− mice than in WT mice. In addition, WT mice but not IL-5−/− mice had raised levels of eosinophils in their peripheral blood between days 5 and 8 following infection. Oral administration of Nω-nitro-l-arginine methyl (from day 4 postinfection) increased mortality rates in both IL-5−/− and WT mice, indicating a protective role for nitric oxide during the early stages of oral T. gondii infection. In comparison with oral infection, no difference in mortality was observed between IL-5−/− and WT mice following intraperitoneal infection with T. gondii, with all mice surviving until 35 days postinfection. Similarly, no significant differences were observed in the severity of the meningitis, perivascular cuffing, or number of microglial nodules or parasites in the brains of intraperitoneally infected mice. Together, these results demonstrate a detrimental role for IL-5 during the early stage of oral infection with T. gondii which is associated with increased small-intestine pathology, eosinophilia, and reduced plasma IL-12 and IFN-γ levels.